Awareness and Skills of Libyan Physicians in Delivering Bad News to Patients at Tripoli University Hospital - Najat Alfaires; Aida Elkituni (AlQalam Journal of Medical and Applied Sciences, 2024)
Breaking bad news (BBN) to patients is a highly sensitive challenge that, sooner or later, all physicians must face. It is one of the most difficult responsibilities in the practice of medicine. Physicians should learn good communication techniques to assist patients in overcoming negative news. Therefore, the study is presented to evaluate the awareness and skills of Libyan physicians in delivering bad news to their patients. A cross-sectional study was carried out at Tripoli University Hospital (TUH) from the first of April 2021 until the last of July 2022. In Libya, a structured questionnaire based on the 6-step SPIKES protocol for BBN was administered to 150 physicians working at the TUH to assess their awareness and training. About 46% of the physicians had good awareness of the components of the 6-step SPIKES protocol, while 53% implemented the protocol at the accepted level. There was statistical significance between awareness level, age, and gender. There was no significant relation among physicians with regards to their qualifications, physicians with PhD degrees, or registrar, and medical officers about awareness and practice scores. There is a weak positive correlation between the awareness group score and the training group score (r=0.20. p=0.015). Physicians’ BBN awareness is at an accepted level, and their method of practice is accepted as well. BBN is a neglected topic in medical education and training, especially among physicians under the age of 31. يعد نقل الأخبار السيئة للمرضى تحديًا حساسًا للغاية يجب على جميع الأطباء مواجهته عاجلاً أم آجلاً. إنها واحدة من أصعب المسؤوليات في ممارسة الطب. يجب أن يتعلم الأطباء تقنيات التواصل الجيدة لمساعدة المرضى في التغلب على الأخبار السلبية. ولذلك، تهدف الدراسة إلى تقييم وعي ومهارات الأطباء الليبيين في إيصال الأخبار السيئة إلى مرضاهم. تم إجراء دراسة مقطعية في مستشفى جامعة طرابلس في الفترة من الأول من أبريل 2021 حتى الأخير من يوليو 2022. في ليبيا، تم إجراء استبيان منظم يعتمد على بروتوكول SPIKES المكون من 6 خطوات لـنقل الاخبار السئية على 150 طبيبًا يعملون في مستشفي جامعة طرابلس لتقييم وعيهم وتدريبهم. كان لدى حوالي 46% من الأطباء وعي جيد بمكونات بروتوكول SPIKES المكون من 6 خطوات، بينما قام 53% بتنفيذ البروتوكول على المستوى المقبول. وكانت هناك دلالة إحصائية بين مستوى الوعي والعمر والجنس. لم تكن هناك علاقة ذات دلالة إحصائية بين الأطباء فيما يتعلق بمؤهلاتهم، والأطباء الحاصلين على درجة الدكتوراه، أو المسجل، والموظفين الطبيين حول درجات الوعي والممارسة. توجد علاقة ارتباطية ضعيفة موجبة بين درجة مجموعة الوعي ودرجة مجموعة التدريب (r=0.20.p=0.015). إن وعي الأطباء بـ نقل الاخبار السئية عند مستوى مقبول، كما أن طريقة ممارستهم مقبولة أيضًا. يعد نقل الاخبار السئية موضوعًا مهملاً في التعليم والتدريب الطبي، خاصة بين الأطباء الذين تقل أعمارهم عن 31 عامًا